Faktor Yang Mempengaruhi Produksi Tembakau (Nicotiana tabacum) Di Kecamatan Sulang Kabupaten Rembang - Astuti, Dessriana Eka Widi; Supardi, Suprapti; Awami, Shofia Nur; Hastuti, Dewi (Jurnal Social Economic of Agriculture, 2021)
This study aims to determine the factors that influence tobacco production and determine the level of efficient use of inputs on tobacco production factors. This research uses a stratified random sampling method with 63 farmers as respondents. The analysis used is multiple linear regression and calculation of economic efficiency. The results stated that the R2 value obtained through multiple linear regression analysis was 0.890, meaning that the contribution of independent variables (land area, number of laborers, number of seedlings, amount of TSP fertilizer, amount of ZA fertilizer, amount of ZK fertilizer, number of pesticides) to tobacco production was 89 percent, while 11 percent is influenced by other variables outside the model. The results of the F-test were jointly influential and the t-test showed variables that influenced tobacco production including land area, number of laborers, number of seeds, amount of ZA fertilizer, and amount of pesticides. Variables such as the amount of TSP fertilizer and the amount of ZK fertilizer had no significant effect. The use of production factors in tobacco farming has not been efficient. Keywords: Efficiency, Production, Tobacco.